Linguapoetics is a Branch of Philology (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article is due to the need to study and comprehend the texts themselves, which still exists, despite the availability of numerous works devoted to the study of the Shakespearean period. In these studies, either genres of Shakespearean sonnets, or stylistic features of texts, or the issue of influences and borrowings and the ideological and artistic content of works are studied, but they do not conduct lingua-poetic analysis that contributes to a better understanding of texts in the unity of their form and content. This problem and some other questions regarding the artistic value of the sonnets can now be solved by means of lingua-poetics of narrative types. Keywords: Lingua-poetics, Shakespearean sonnets, Narrative types, “description”, “reasoning”, “expression of will”, stylistically labeled, rhetorical devices, labeled linguistic units, metasemiotic properties.